Optimalisasi Pengendalian Kas dan Persediaan pada Usaha Cafe Multiproduk melalui Pelatihan Akuntansi Praktis di Locana & More Medan - Mutia Riska Faridani; Sovia Lolita Apriani Pardede; Corinna Wongsosudono; Ripka Seriidahnaita Ginting; Esty Pudyastuti; Rifdah Riyan Dara (Jurnal Masyarakat Indonesia (Jumas), 2025)
This Community Service Program aims to improve cash control and inventory management at Locana & More, a multiproduct café business that also sells flowers and fashion items. The partner’s main problems include the absence of a structured cash recording system, inconsistent transaction documentation, and the lack of inventory records, which resulted in discrepancies between physical stock and written records. The program was carried out using a participatory approach and hands-on practice, actively involving the owner and employees in practical accounting training. The training covered daily cash books, cash journals, transaction documentation, stock cards, and scheduled Stock Opname. The results indicate significant improvements in recording consistency, stock accuracy, and employees’ understanding of basic accounting procedures. In addition, the program produced a Standard Operating Procedure (SOP) for cash and inventory control that can be applied sustainably. Overall, the program positively strengthened internal control systems and enhanced operational efficiency.